2010
DOI: 10.1088/1475-7516/2010/03/031
|View full text |Cite
|
Sign up to set email alerts
|

Observational constraints on holographic dark energy with varying gravitational constant

Abstract: We use observational data from Type Ia Supernovae (SN), Baryon Acoustic Oscillations (BAO), Cosmic Microwave Background (CMB) and observational Hubble data (OHD), and the Markov Chain Monte Carlo (MCMC) method, to constrain the cosmological scenario of holographic dark energy with varying gravitational constant. We consider both flat and non-flat background geometry, and we present the corresponding constraints and contour-plots of the model parameters. We conclude that the scenario is compatible with observat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
49
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 121 publications
(61 citation statements)
references
References 113 publications
12
49
0
Order By: Relevance
“…In addition, it is shown that DE takes up about two-thirds of the total energy density from cosmic observations. In theory many kinds of DE models [5][6][7][8][9][10][11][12][13][14][15] have already been constructed to explore the DE properties.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is shown that DE takes up about two-thirds of the total energy density from cosmic observations. In theory many kinds of DE models [5][6][7][8][9][10][11][12][13][14][15] have already been constructed to explore the DE properties.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, correspondences are established between HDE and other scalar field models of DE [37][38][39] while in other studies, HDE is studied in alternative gravity theories like Braneworld, f (R), scalar-tensor gravity, Brans-Dicke (BD) and DGP model etc [40][41][42][43][44][45][46][47][48][49][50]. The HDE also best fits with the observational data of CMB and supernova of type Ia [51][52][53][54][55][56].…”
Section: Introductionmentioning
confidence: 61%
“…It was also demonstrated that the HDE model can fit well cosmological data obtained thanks to observations of both CMB radiation anisotropies and SNeIa [76][77][78].…”
Section: Introductionmentioning
confidence: 74%